2016
DOI: 10.1515/hsz-2015-0261
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of loop 5 lysine residues and the N-terminal β-hairpin of the ribotoxin hirsutellin A on its insecticidal activity

Abstract: represented by RNase T1. They share a high degree of sequence identity and a common structural fold, including the geometric arrangement of their active sites. However, ribotoxins are larger, with a well-defined N-terminal β-hairpin, and display longer and positively charged unstructured loops. These structural differences account for their cytotoxic properties. Unexpectedly, the discovery of hirsutellin A (HtA), a ribotoxin produced by the invertebrate pathogen Hirsutella thompsonii, showed how it was possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The equivalent residues in HtA (His 42, Glu 66 and His 113) were identified by structural comparison, showing that the catalytic residues are conserved, but also presenting other features closer to the T1-like RNases (Phe 126 instead of the equivalent Leu 145, for example) or even some others which were completely new (Asp 40 instead of Tyr 48) [ 31 ] ( Figure 1 B). Mutagenesis studies have indeed revealed that the active site of HtA would provide a more adaptable microenvironment than the one described for α-sarcin being able to better accommodate electrostatic and structural changes [ 31 , 32 , 33 ].…”
Section: Fungal Ribotoxinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The equivalent residues in HtA (His 42, Glu 66 and His 113) were identified by structural comparison, showing that the catalytic residues are conserved, but also presenting other features closer to the T1-like RNases (Phe 126 instead of the equivalent Leu 145, for example) or even some others which were completely new (Asp 40 instead of Tyr 48) [ 31 ] ( Figure 1 B). Mutagenesis studies have indeed revealed that the active site of HtA would provide a more adaptable microenvironment than the one described for α-sarcin being able to better accommodate electrostatic and structural changes [ 31 , 32 , 33 ].…”
Section: Fungal Ribotoxinsmentioning
confidence: 99%
“…It is in this region where HtA and restrictocin show more variability when compared to α-sarcin. The N-terminal β-hairpin of HtA is much shorter ( Figure 1 ), but this truncation appears to be compensated by the extension of loop 5, which also exhibits a higher amount of positive charges [ 32 , 33 ].…”
Section: Fungal Ribotoxinsmentioning
confidence: 99%
See 1 more Smart Citation